The role of tumor necrosis factor-alpha (TNF-α) inhibitor in steven johnson syndrome/toxic epidermal necrolysis (SJS/TEN) management: a systematic review - Kurnia, Icasia Yuseli (Intisari Sains Medis (ISM) (Manado), 2022)
Background. Steven Johnson Syndrome and Toxic Epidermal Necrolysis are dermatologic emergencies with high mortality rates characterized by extensive skin involvement. TNF-α has a role in inducing the production of granulysin that enhances keratinocyte cell death. Thus, the use of TNF-α inhibitors such as etanercept and infliximab is promising to halt the disease progression. This systematic review aims to evaluate the efficacy of TNF-α inhibitor in SJS/TEN management. Method. A systematic review using an online database was conducted based on PRISMA guidelines. Inclusion criteria were studied about the role of TNF-α inhibitor in SJS/TEN management. The exclusion criteria were a letter to the editor, commentary report, review, meta-analysis, study not used humans as a study subject, not available in full text and not in English or Bahasa Indonesia. Result. Fourteen studies are included in this systematic review consisting of ten case reports, three cohort retrospective studies, and one randomized controlled trial. TNF-α inhibitors such as etanercept and infliximab are beneficial for SJS/TEN management because they accelerate skin healing time and re-epithelization, reduce in-hospital duration and mortality rate, and minimal complications and side effects. TNF-α inhibitors should be given quickly after the disease onset, and combination with other immunosuppressive agents should be avoided to prevent the excessive immunosuppressive effect. Conclusion. TNF-α inhibitors such as etanercept and infliximab promise therapy to halt SJS/TEN progression.